(untitled) (Journal of the College of Education for Women, 2019)
The research deals with Iraq’s position of the Lebanese civil war and the Efforts made by Iraq in order to stop the bleeding of this war, the research also deals with the nature of regime in Lebanon and the developments that preceded the war and the positions of the internal and external competing forces, as weu as handling the Iraqi Syrian disagreement and it’s impaet on the situation of Lebanon and the war developments.The research focused on the Iraq’s position towards the externd proposed solutions to solve the Lebanese civil war.